Wolfblood. Season one - Kelly, Aimme; Lockwood, Bobby; Williams-Stirling, Kedar; Flatiron Film Company; British Broadcasting Corporation; Cinedigm (Firm) ([London] : BBC, 2012)
Being a teenager is hard enough. Being a Wolfblood teenager is ten times more complicated. Fourteen-year-old Maddy loves her abilities, heightened senses, being faster, stronger and more graceful, but hates the secrets that come with them. And when a new boy starts at Maddy's school, she learns that her family isn't the only Wolfbloods in town.
Disc 1 (episodes 1-7): Lone wolf -- Mysterious developments -- Family ties -- Cry wolf -- Occam's razor -- Maddy cool! -- Dark moon. Disc 2 (episodes 8-13): Wolfsbane -- A quiet night in -- Call of the wild -- Eolas -- Caged -- Irresistible -- Bonus features.
Bonus features: Behind-the-scenes; Interviews with the cast; meet your favorite characters.
Aimme Kelly, Bobby Lockwood, Kedar Williams-Stirling.
DVD, widescreen.
Closed captioned for the hearing impaired.
Keywords: Teenagers -- Juvenile drama; Supernatural -- Juvenile drama; Werewolves -- Juvenile drama; Feature films; Fiction films; Children's films; Children's television programs; Video recordings for the hearing impaired